ATM 2016
DOI: 10.20937/atm.2016.29.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Determining heavy metal contamination of road dust in Delhi, India

Abstract: RESUMENLa contaminación del aire es considerada como uno de los mayores desafíos ambientales debido a sus efectos sobre los ecosistemas y la salud humana. En este estudio se investigan los niveles de concentración y las fuentes de la contaminación por metales pesados en muestras de polvo de caminos recolectadas en varios sitios que incluyen áreas con cuatro actividades diferentes en Delhi, India: industriales, carreteras, residenciales y de uso mixto. El contenido de metales en polvo de caminos se analizó medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…Heavy metals associated pollution in relation to road deposited sediment or in any sediment are well documented in the literature [31,32]. In this study, assessment of contamination of suspended/re-suspended road dust collected from road side plants, road barriers, road islands were performed taking several indicators, such as contamination factor (C f ), degree of contamination (C deg ), potential ecological risk index (RI), pollution index (PI) and integrated pollution index (IPI) in a hierarchy level.…”
Section: Heavy Metal Pollution Assessmentmentioning
confidence: 99%
“…Heavy metals associated pollution in relation to road deposited sediment or in any sediment are well documented in the literature [31,32]. In this study, assessment of contamination of suspended/re-suspended road dust collected from road side plants, road barriers, road islands were performed taking several indicators, such as contamination factor (C f ), degree of contamination (C deg ), potential ecological risk index (RI), pollution index (PI) and integrated pollution index (IPI) in a hierarchy level.…”
Section: Heavy Metal Pollution Assessmentmentioning
confidence: 99%
“…PC-2 also had moderate loading on Co. Co and Cr formed the cobalt-chromium (CoCr) alloy which is used in engine components and many other industrial or mechanical components where high wear-resistance is required [58]. PC-3 explained 15.5% of the total variance and dominated by SOM, Ca and P. This dipolar factor presents moderate positive loading of SOM and moderate negative loadings of Ca and P. Suryawanshi et al [59] working on road dust of Delhi confirmed loadings of Cu and Pb on PC-1. They suggested that particles released due to traffic activities are responsible for their contents.…”
Section: Multivariate Statistical Approachmentioning
confidence: 99%
“…Various studies outside Nigeria such as that of Obaidullah et al, (2015) characterized indoor PM into three sizes of particles such as PM1, PM2.5 and PM10 at three different enclosed parking garages in two cities of Belgium with varying vehicle intensity and varying layout with results indicating average particles mass concentrations in garages ranging from 28 µg/Nm 3 to 50 µg/Nm 3 for PM1, 43 µg/Nm 3 to 60 µg/Nm 3 for PM2.5 and 58 µg/Nm 3 to 90 µg/Nm 3 for PM10. Suryawanshi et al, (2016) measured the concentration levels and sources of heavy metals contamination in road dust samples collected from industrial, highways, residential and mixed use in Delhi, India. Metal content in road dust was analyzed with results indicating high concentration levels of Ni, Cr and Pb in industrial areas.…”
Section: Introductionmentioning
confidence: 99%